TEKNIK INKUBASI TELUR MENGGUNAKAN SISTEM TRAY BERTINGKAT UNTUK MENINGKATKAN DAYA TETAS TELUR IKAN SEMAH (Tor douronensis) - E. Mulyati Effendi; Ikhsan Pratama; Jojo Subagja (Universitas Pakuan, 2015)
Fish eggs semah in cultivating on average only hatch of 67%, so still far stated well and need to do a proper egg incubation technique to increase the degree of hatching. Efforts are being made at other hatcheries as Catfish is using the technique of egg incubation method of stagnant water and MacDonald jars, but this system still has flaws, that can lead to poor water quality (stagnant water) and the presence of abnormal larvae (Mac Donald jars). In this study, the technique of egg incubation is carried out using a multilevel system tray modification. The results of the use of multilevel system tray in Aquarium shows very different real power against egg hatch (HR) fish semah, whereas against an increase in the degree of abnormality of fish larvae semah influence is relatively the same.The use of 3-floor tray (A3), can enhance degrees most high 89.19% hatching, larval fish and the degree of abnormality 1.63%. Key words : System tray multilevel, tetas power eggs (HR), the degree of abnormality, Tor douronensis